Pengaruh Price Discount dan Bonus Pack TerhadapImpulse Buying Konsumen Indomaret di Kecamatan Lawang Kabupaten Malang - Rossi Intan Sari; M Fakhruddin Mudzakkir; Sri Wilujeng (Jurnal Riset Mahasiswa Manajemen, 2018)
This study aims to determine (1) the effect of price discounts on Indomaret consumer impulse buying in Lawang District of Malang Regency and (2) the effect of bonus packs on Indomaret consumer impulse buying in Lawang District of Malang Regency. This research was conducted at the Indomaret minimarket in Lawang District Malang Regency, for primary data collected through the distribution of questionnaires to 100 respondents using accidental sampling method with the criteria that respondents had made an impulse buying purchase in Indomaret Lawang District. Data collection in the study only used 3 villages namely Bedali, Kalirejo and Lawang villages from 12 villages in Lawang Subdistrict, to facilitate and shorten the time in data collection. The analysis technique used is Multiple Linear Regression. Based on the results of the analysis of the effect of price discounts and bonus packs on impulse buying, it can be concluded that price discounts do not have a positive and significant effect on impulse buying and bonus packs have a positive and significant effect on impulse buying.